Snail/Slug family of repressors: slowly going into the fast lane of development and cancer. - Hemavathy, K.; Ashraf, S.I.; Ip, Y.T. (Gene, 2000)
The existence of homologous genes in diverse species is intriguing. A detailed comparison of the structure and function of gene families may provide important insights into gene regulation and evolution. An unproven assumption is that homologous genes have a common ancestor. During evolution, the original function of the ancestral gene might be retained in the different species which evolved along separate courses. In addition, new functions could have developed as the sequence began to diverge. This may also explain partly the presence of multipurpose genes, which have multiple functions at different stages of development and in different tissues. The Drosophila gene snail is a multipurpose gene; it has been demonstrated that snail is critical for mesoderm formation, for CNS development, and for wing cell fate determination. The related vertebrate Snail and Slug genes have also been proposed to participate in mesoderm formation, neural crest cell migration, carcinogenesis, and apoptosis. In this review, we will discuss the Snail/Slug family of regulators in species ranging from insect to human. We will present the protein structures, expression patterns, and functions based on molecular genetic analyses. We will also include the studies that helped to elucidate the molecular mechanisms of repression and the relationship between the conserved and divergent functions of these genes. Moreover, the studies may enable us to trace the evolution of this gene family.